Regulation of mammalian Ste20 (Mst) kinases. Issue 3 (March 2015) - Rawat, Sonali J.; Chernoff, Jonathan
Highlights Mst1/Mst2/Hippo are core, conserved components of a tumor suppressor pathway. Mst/Hippo signaling has both similarities and key differences between mammals and flies. Homo- and heterodimerization play important roles in Mst regulation.